From Socratic Behaviourism to Digital Constructivism - Diogo dos Reis, António Manuel; Yakovleva, Olga; Smyrnova-Trybulska, Eugenia; Morze, Nataliia (International Journal of Research in E-learning, 2018)
The paper presents a synopsis of the evolution of methods and techniques up to the digital age and characterises the main aspects of behaviourist and constructivist models in order to study the development of new advanced pedagogical tools and methods in education science in constructivist environment. For the purpose of the study, an analysis of the technological evolution during the last decades and its impact on education science was made, with a special focus on virtual teaching and learning. The practical outcome of the study was a series of online seminars and workshops, prepared by the international team of the IRNet project. The keynotes and workshops were held during DLCC2017 Conference (Theoretical and Practical Aspects of Distance Learning, subtitle: Effective Development of Teachers’ Skills in the Area of ICT and E-learning) at the University of Silesia in Katowice, Poland. Video presentations and an automatic translation are available at: https://areis-en-constructivism.blogspot.pt.